(untitled) (Journal of Applied Juvenile Justice Services, 2019)
Multidisciplinary collaboration is paramount to engendering efficacious juvenile reentry. As the lives of juvenile offenders are infused with interwoven complexities and traumas leading to involvement with the juvenile justice system, a multifaceted approach permeated with varying perspectives is imperative. Effective juvenile reentry partnerships must embrace inclusivity and distinctly capitalize on the wide-ranging expertise encapsulated within a multidisciplinary team. Multidisciplinary collaboration is vital for juvenile offenders to return to the community from confinement with a comprehensive understanding of their situation as well as an assortment of approaches to mitigating their challenges both within and outside of the juvenile justice system. This manuscript will describe a unique approach and promising strategies designed to foster a smooth transition of urban juvenile offenders from confinement at a short-term detention facility back into the community. Lessons learned from a multidisciplinary collaboration between school districts, probation, health care, and city agencies designed to support juvenile reentry will be highlighted. Implications for replication among collaborative partners within the context of juvenile justice systems will be discussed.